Assessment Report on Bali Clan (Two maps), Bamenda Division (Colonial Letters and the Contact of Knowledges, 1925)
This file contains colonial assessment reports including two maps on Bali Clan, Bamenda Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Bali; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies